Identity Conflict with Cross-Border Spillovers - Dripto Bakshi; Indraneel Dasgupta (Institute for the Study of Labor (IZA), 2016)
We model simultaneous inter and within identity-group conflict in two territories connected by cross-territorial spill-overs. Within each territory, two groups contest the division of a group-specific public good, and all members contest the division of group income. Each group has a cross-border affiliate. Greater success (share) of its affiliate 'spills over' into higher efficiency of a group in inter-group conflict. We find that inter-group and total conflict move together within a territory, while within-group conflict and output move in the opposite direction. A unilateral increase in cross-border spill-over reduces inter-group conflict in the source territory but increases it in the destination; an equi-proportionate bilateral increase affects conflict in a non-monotone manner. Population increase in a territory, a larger minority, weaker property rights, higher relative labour productivity of the majority, may all increase inter-group conflict in the other territory. Community-neutral growth in labour productivity within a territory reduces inter-group conflict therein.
Keywords: D72; D74; O10; O20; 330; ethnic conflict; identity; simultaneous between and within group contest; cross-border spillover; globalization; ethnic polarization; community-biased growth